THE CULTURE OF SECRECY IN THE DIGITAL AGE: BETWEEN NECESSITY, ABUSE, AND CYBERSECURITY - Matić, Goran (National interest, 2025)
The culture of secrecy represents an institutionalized model of information management that has evolved from ancient civilizations to modern digital societies. Historically, secrecy was justified by security and political interests, but it often transformed into a mechanism for concentrating power and restricting democratic oversight (Greenwald, No Place to Hide, 2014, 45–60). In the Roman Empire, information was safeguarded in formal archives (tabularia), while the Qin and Han dynasties in China developed complex bureaucratic systems for managing confidential data. Modern secrecy mechanisms, such as the D-Notice system in the United Kingdom, continue to institutionalize information control. The digital transformation has expanded the concept of secrecy through algorithms and mass surveillance, enabling new methods of concealing and manipulating data. Examples such as the misuse of Pegasus spyware or the mass classification of public contracts illustrate how technology not only facilitates information management but also enables more subtle forms of secrecy. At the same time, whistleblowers like Edward Snowden highlight the vulnerabilities of digital privacy, while legal mechanisms such as the Freedom of Information Act (FOIA) in the U.S. and initiatives for document declassification promote transparency.This paper analyzes the historical development of the culture of secrecy, its transformation in the digital age, and contemporary challenges in balancing legitimate security protection with the need for transparency. Special attention is given to public control mechanisms, including freedom of information, declassification processes, and the role of whistleblowers in preserving transparency as a fundamental element of democratic society.
Keywords: politics; security; secrecy culture; cybersecurity; digital society; public interest; data protection; transparency